L'Impact de la crise economique sur les systemes agricoles et la changement du couvert forestier dans la zone forestiere humide du Cameroun - Bikie, H.; Ndoye, O.; Sunderlin, William D. (Center for International Forestry Research, 2000)
A sample survey of 648 households was conducted in 54 villages in the humid forest zone of Cameroon to understand the effect of the economic crisis (dating from 1986) and the 1994 currency devaluation on the practices of small farmers, and the effect of these practices on forest cover change. Four hypotheses were tested concerning: the balance between plantation crop and food crop production; the degree of market-orientation of food crop production; the gender division of labour; and the degree of dependence on non-timber forest products (NTFPs). Some key findings are: (1) the area of cocoa production has stagnated while that of coffee, plantain, and other food crops has tended to increase; (2) food crop production is now more market-oriented; (3) men are now far more involved in food crop production than in the past; (4) more households now exploit NTFPs than before but it remains a small source of income; and (5) in connection with these changes, there has been an overall increase in the rate of forest clearing by small farmers. The study concludes that economic crises and macroeconomic policies can have unexpected and powerful effects on land use and forest practices. Future policies aimed at improving forest conservation and management must take account of this fact.